Latency to Reward Predicts Social Dominance in Rats: A Causal Role for the Dopaminergic Mesolimbic System - Lozano-Montes, Laura; Astori, Simone; Abad, Sonia; Guillot de Suduiraut, Isabelle; Sandi, Carmen; Zalachoras, Ioannis (Frontiers in Behavioral Neuroscience, 2019)
Reward signals encoded in the mesolimbic dopaminergic system guide approach/seeking behaviors to all varieties of life-supporting stimuli (rewards). Differences in dopamine levels have been found between dominant and submissive animals. However, it is still unclear whether these differences arise as a consequence of the rewarding nature of the acquisition of a dominant rank, or whether they preexist and favor dominance by promoting reward-seeking behavior. Given that acquisition of a social rank determines animals’ priority access to resources, we hypothesized that reward-seeking behavior might affect hierarchy establishment, and that modulation of the dopaminergic system could affect the outcome of social competition. We characterized reward-seeking behaviors based on rats’ latency to get a palatable-reward when given temporary access to it. Subsequently, rats exhibiting short (SL) and long (LL) latency to get the rewards cohabitated for more than two weeks, in order to establish a stable hierarchy. We found that SL animals exhibited dominant behavior consistently in social competition tests (for palatable-rewards and two water competition tests) after hierarchy was established, indicating that individual latency to rewards predicted dominance. Moreover, because SL animals showed higher mesolimbic levels of dopamine than LL rats, we tested whether stimulation of mesolimbic dopamine neurons could affect the outcome of a social competition. Indeed, a combination of optical stimulation of mesolimbic dopamine neurons during individual training and during a social competition test for palatable rewards resulted in improved performance on this test.